Operating Room Orientation Using Visual Media Virtual Reality Box (Vr.Box) On Decreasing The Level of Fear of Pre Operation Patients - Hidayat, Wahyu; Sukmaningtyas, Wilis; Bisma Yudha, Magenda (Global Indonesia Health Care (GOICARE), 2024)
Background: Effective new patient orientation is crucial in reducing preoperative anxiety, which can significantly impact patient outcomes. Anxiety in patients often stems from unmet needs for security and fear of imminent threats. The Virtual Reality Box (VR Box) has emerged as a potential tool to alleviate this anxiety by providing a distracting and calming experience. Purposes: This study evaluates the impact of operating room orientation on preoperative anxiety levels, with a focus on its effectiveness when combined with VR Box technology. Methods: This study utilized the Amsterdam Preoperative Anxiety and Information Scale (APAIS) to measure anxiety levels in patients before and after receiving operating room orientation. The intervention involved providing comprehensive orientation about the nursing process and surgical environment. A total of [number] preoperative patients participated in the study, and their anxiety levels were assessed pre- and post-orientation. Findings: The analysis revealed a reduction in average anxiety levels from 20.1% before the orientation to 16.2% after the orientation, indicating a 3.9% decrease in anxiety. This suggests that the orientation process effectively mitigated some of the anxiety associated with preoperative procedures. Conclusion: The findings demonstrate that operating room orientation can significantly reduce preoperative anxiety. The integration of orientation strategies with tools such as the VR Box could enhance patient comfort and preparedness, potentially improving overall surgical outcomes. Future research should explore the long-term benefits and potential enhancements of combining orientation with advanced anxiety-reducing technology.